Onomastic awareness in Vincent Pol’s works - Bryła, Władysława (Name – style – text: A jubilee book dedicated to Professor Elżebieta Umińska-Tytoń, 2023)
The author presents Vincent Pol’s (1807‒1872) fascination with Polish folk names from a geographical and botanical domain. Pol argues that such names are well-suited and constitute a source of information about the world. He postulates that regional and folk names should be included in academic descriptions.